KONSEP MUTHLAQ DAN MUQAYYAD DALAM AL-QUR’AN - Fadhila Sidiq Permana (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
Understanding the typology of the meanings of Quranic verses is very important for beginners who want to deepen their study of Quranic exegesis. Failure to understand the meanings of the Quran can result in individuals or groups adopting radical views that tend to be intolerant in religious attitudes and perspectives. This article discusses the concepts of muthlaq and muqayyad contained in the holy Quran. One of the conclusions of this study explains that the function of muqayyad evidence is to serve as a limitation for muthlaq evidence. When muthlaq and muqayyad evidence have differences in the target of the ruling (mahkum bih) or in the cause of the ruling, muthlaq evidence must be directed towards muqayyad evidence using the theory of qiyas.